Mobile applications aiming to facilitate immigrants' societal integration and overall level of integration, health and mental health. Does artificial intelligence enhance outcomes? - Nick Drydakis (Global Labor Organization (GLO), 2020)
Using panel data on immigrant populations from European, Asian and African countries the study estimates positive associations between the number of mobile applications in use aiming to facilitate immigrants' societal integration (m-Integration) and increased level of integration (Ethnosizer), good overall health (EQ-VAS) and mental health (CESD-20). It is estimated that the patterns are gender sensitive. In addition, it is found that m-Integration applications in relation to translation and voice assistants, public services, and medical services provide the highest returns on immigrants' level of integration, health/mental health status. For instance, translation and voice assistant applications are associated with a 4% increase in integration and a 0.8% increase in good overall health. Moreover, m-Integration applications aided by artificial intelligence (AI) are associated with increased health/mental health and integration levels among immigrants. We indicate that AI by providing customized search results, peer reviewed e-learning, professional coaching on pronunciation, real-time translations, and virtual communication for finding possible explanations for health conditions might bring better quality services facilitating immigrants' needs. This is the first known study to introduce the term `m-Integration', quantify associations between applications, health/mental health and integration for immigrants, and assess AI's role in enhancing the aforementioned outcomes.
Keywords: O3; O31; I1; J15; 330; Mobile Applications; m-Integration; m-Health; Artificial Intelligence; Integration; Immigrants; Refugees; Health; Mental Health